Self-evaluated competences of multidisciplinary students before and after professional specialisation education in digital social and health care services - Ahonen, Outi Maria; Sanerma, Päivi; Rauha, Anna; Naakka, Hanna; Perälä, Sami; Paldanius, Mika; Heinonen, Jarmo (Finnish Journal of eHealth and eWelfare, 2024)
The integration of separate service systems, digitalisation, demographic changes, and staff shortages has increased the need for systematic and flexible skills development in social and health care services. In today’s working life, learning and development take place in ecosystems. This study aimed to evaluate and identify differences between students’ self-assessed competences and their beliefs about the importance of competence areas before and after professional specialisation education (PSE). The research questions were: 1) Was there any difference in students’ self-evaluated level of multidisciplinary competences before and after professional specialisation education? 2) Based on students’ self-evaluations, was there any difference between the multidisciplinary competences they considered important before and after professional specialisation education? Analysis of variance (ANOVA) test and paired t-tests were used to examine the differences in the subjects’ spontaneous responses about whether they had experienced a change in their competences after undertaking specialisation education. In the initial survey (N = 274), the student respondent group was 180, and the total number of student pairs was 65. The initial and final measurements of the 65 students who responded to the follow-up survey were therefore comparable. Four-point Likert scales were used in the questionnaires. The modified questionnaire was designed so that students answered each of the competences at two levels from their own perspectives. First, they described how important the acquisition of the skills described in this sentence would be for their own professional competence. Then, they assessed their current level of competence in relation to the sentence in question. There were no statistical differences (p>0.05) between measurements taken before and after education in most of the qualification statements describing importance. There were statistical differences (p<0.05) between the initial (before education) and post-training measurements (after education) for all statements describing self-assessment competences. According to this study, even micro-credentials promoted learning. In learning, ecosystem and perceived importance support the level of digital maturity of organisations.